Chapter Making a site otherwise inaccessible accessible: 3D laser scanner scanning of the Grotta dei Cervi di Porto Badisco in Otranto (Le) - Muscatello, Giovanna (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The Grotta dei Cervi in Porto Badisco, Otranto (Le) (Italy), is one of the most important monuments of post- paleolithic wall art in the Mediterranean. Currently, thanks to the 3D laser scanner survey carried out in the cave, there is a complete documentation, a digital archive that collects a database from which it is possible to extrapolate data regarding the morphology of the cave complex and the spatial location. Mapping of the corpus of pictograms, it is possible to digitally preserve the figurative apparatus, which has been and still is being studied by numerous scholars.